Flipping Shells! Unwinding LR Asymmetry in Mirror-Image Molluscs. Issue 3 (March 2020) - Davison, Angus
Abstract : In seeking to understand the establishment of left–right (LR) asymmetry, a limiting factor is that most animals are ordinarily invariant in their asymmetry, except when manipulated or mutated. It is therefore surprising that the wider scientific field does not appear to fully appreciate the remarkable fact that normal development in molluscs, especially snails, can flip between two chiral types without pathology. Here, I describe recent progress in understanding the evolution, development, and genetics of chiral variation in snails, and place it in context with other animals. I argue that the natural variation of snails is a crucial resource towards understanding the invariance in other animal groups and, ultimately, will be key in revealing the common factors that define cellular and organismal LR asymmetry. Highlights: Snails are the only animal group to ordinarily produce mirror-image forms. They have the potential to be an unequalled natural genetic resource in understanding chirality, including the invariant LR asymmetry of other animal groups. A formin gene is associated with variation in LR asymmetry in two snail species, although the mutation is pathological in both. The genes that produce chiral variation without pathology are still wholly unknown; changes in gene expression or of accessory factors are likely. Understanding LR asymmetry in snails will involve studies of early embryology and genomics, alongside whole-animal studies on the impact of natural and sexual selection. Chiral variation in snails may be enabled by the dichotomous nature of spiralian cleavage (dextral or sinistral), combined with the action of selection on the outward shell phenotype.